Landscape architecture at Wageningen (Netherlands) - Martin van den Toorn (Projets de Paysage)
In this article, I will give a brief overview of the development of teaching and research in landscape architecture in Wageningen by studying the relationships between practice, education and research over the past 50 years. The purpose of this article is to provide a first explorative overview. So far, few – if any – publications exist on this issue in an international context. The research method is based on the principles of case study research, logical argumentation and comparative analysis. The research material is largely Dutch; publications, projects. The outline is made up of three main sections, based on development over the last 50 years of landscape architecture education in Wageningen. New design knowledge and work domains for a growing number of landscape architects have emerged over the last 50 years. The academic environment of Wageningen University has strengthened the position of landscape architecture in meeting the new challenges of climate change; the combination of knowledge of the landscape as a natural system and conceptual ways of thinking seems to be a unique and solid basis for the future.